2018
DOI: 10.1007/s10508-018-1169-8
|View full text |Cite
|
Sign up to set email alerts
|

Physical Health Disparities Across Dimensions of Sexual Orientation, Race/Ethnicity, and Sex: Evidence for Increased Risk Among Bisexual Adults

Abstract: Accumulating evidence suggests that sexual minority individuals are at increased risk for physical health conditions compared to heterosexual individuals. However, we know little about physical health disparities affecting bisexual individuals, a population at increased risk for psychiatric and substance use conditions compared to both heterosexual and lesbian/gay populations. Using a large, nationally representative sample, we examined physical health disparities for bisexual individuals. To advance research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 78 publications
1
43
0
Order By: Relevance
“…A recent study conducted by Dyar et al found that bisexualidentified men had higher rates of self-reported obesity, high total cholesterol, and hypertension than heterosexual men. 50 We did not identify significant differences for high total cholesterol. However, our findings were consistent for obesity and hypertension.…”
Section: Discussionmentioning
confidence: 68%
“…A recent study conducted by Dyar et al found that bisexualidentified men had higher rates of self-reported obesity, high total cholesterol, and hypertension than heterosexual men. 50 We did not identify significant differences for high total cholesterol. However, our findings were consistent for obesity and hypertension.…”
Section: Discussionmentioning
confidence: 68%
“…Nonetheless, bisexual identity is not the driver of mental health disparities per se. Instead, previous studies indicate that individuals who report bisexual identity experience greater levels of bi-negativity from both the heterosexual and lesbian/gay communities [e.g., (58)(59)(60)(61)(62)]. Minority stress drives mental health disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Bisexual individuals are often at increased risk for negative health outcomes compared with heterosexual individuals, as well as lesbian/gay individuals in many cases (Dyar et al, 2019; Feinstein & Dyar, 2017; Taggart et al, 2019). Our results suggest that the observed differences in the diagnosis of BPD between sexual minority and heterosexual patients were largely driven by differences between bisexual and heterosexual patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature documents important differences in outcomes across sexual minority subgroups. Specifically, bisexual individuals routinely evidence worse mental and physical health outcomes compared with lesbian/gay identified individuals (Dyar et al, 2019; Feinstein & Dyar, 2017; Taggart et al, 2019). As such, we further compared prevalence of BPD diagnosis between heterosexual patients and (a) patients who reported lesbian/gay sexual orientation as well as (b) patients who reported bisexual sexual orientation separately.…”
Section: Methodsmentioning
confidence: 99%